A virtual versus blended learning approach to higher education during the COVID-19 pandemic: The experiences of a sport and exercise science student cohort. (June 2022) - Finlay, Mitchell J.; Tinnion, Daniel J.; Simpson, Thomas
Abstract: During the 2020/21 academic year most UK universities rapidly developed learning material as part of a move to blended learning, in response to the COVID-19 pandemic. This was interspersed with periods of virtual-only delivery, aligning with national lockdowns. The previous literature suggests there are both advantages and disadvantages to virtual-only and blended learning approaches, which may impact on student satisfaction. Student satisfaction scores may be especially insightful in a student cohort enrolled on an applied sport programme, whereby practical seminars and assessments would be severely impacted by social restrictions. Therefore, this study aimed to explore the experiences and perceptions of virtual and blended learning approaches in an undergraduate sport and exercise sciences cohort, during the COVID-19 pandemic. Additionally, this study aimed to explore whether student perceptions of both learning modes differed between and within-year groups. Students completed an adapted version of the national student survey (NSS), pertaining to periods of virtual learning-only (n = 81) and blended learning (n = 62). When all students were considered, blended learning yielded consistently higher satisfaction scores across all survey sub-sections (teaching on my course, learning opportunities, assessment and feedback, academic support, organisation and management, learning resources, learning community and student voice) resulting in a significantly higher overall course satisfaction score (3.93 ± 0.99 vs 3.55 ± 1.11; p = 0.33; ES = 0.36). When comparing Year 1 and Year 2 students, the former had significantly higher (p < 0.005) perception scores for teaching on my course, assessment and feedback, academic support, organisation and management, learning resources and learning community, but not learning opportunities, student voice or Covid-19-specific, for the virtual learning survey. Additionally, within-year group (Year 2) differences were found in assessment and feedback, academic support and learning community, with higher perception scores reported in the blended learning survey. No significant within-year group differences were observed in Year 1 students. This study provides the first data on student perceptions of a sport and exercise science programme during blended and virtual learning, amidst a global pandemic. The clear preference for blended learning in the current study, suggests sport and exercise science students appreciated the access to face-to-face teaching, despite the social distancing measures in place. Broadly, the findings may assist in governmental and institutional decision making, and in the designing of learning material during periods of social restrictions. These findings may be more beneficial to the design and implementation of face-to-face and/or online components for more applied, science-based courses. Highlights: Teaching and learning has been severely disrupted by the COVID-19 pandemic. Sport science students perceived blended learning as superior to virtual delivery. A blended learning approach is an effective alternative delivery during social restrictions.